Studie zásobovací logistiky ve zvolené společnosti - Rinnová, Kristýna (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce se zaměřuje na změnu interní logistiky zásobování. Nejdříve jsou uvedeny teoretické poznatky, následně je představena výrobní společnost a analýza současného stavu řízení zásob. Dále jsou navrženy změny pro efektivnější řízení zásob a předpoklady pro realizaci těchto návrhů. V analytické části jsou také vyčísleny přínosy navrženého řešení.

This thesis focuses on changing the internal supply logistic. The first part provides theoretical knowledge, then is indtroduces the production company and analysis of the current state of current management inventory status. Based on the analysis I have proposed measures which are more efficient inventory management. Conditions needed for the implementation of these proposals are proposed as well. The analysis part offers quantified benefits of each proposal.
The Study of Supply Logistics in Selected Company
Keywords: Logistika; Kanban; ABC analýza; řízení zásob; SMART; Logistic; Kanban; ABC Analysis; Supply Management; SMART